2015
DOI: 10.1007/s00127-015-1092-4
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood socioeconomic conditions and depression: a systematic review and meta-analysis

Abstract: We found inconsistent evidence in support of a longitudinal association between NSEC and depression, and heterogeneity according to the length of follow-up time might partly explain the mixed evidence observed in the literature on NSEC and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
116
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(124 citation statements)
references
References 33 publications
7
116
1
Order By: Relevance
“…The first is that we have shown an inverse relationship between household income (an objective measure of socioeconomic status) and depressive symptoms in South Africa, a LMIC country characterized by extreme material deprivation and poverty; a finding that has been previously demonstrated in high-income country contexts (Weich & Lewis, 1998; Lorant et al, 2003; Richardson et al, 2015). This provides further support for evidence showing that poverty is a major risk factor for mental health disorders in LMICs (Patel & Kleinman, 2003; Author et al, 2010; Author et al, 2011; Author, 2014).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The first is that we have shown an inverse relationship between household income (an objective measure of socioeconomic status) and depressive symptoms in South Africa, a LMIC country characterized by extreme material deprivation and poverty; a finding that has been previously demonstrated in high-income country contexts (Weich & Lewis, 1998; Lorant et al, 2003; Richardson et al, 2015). This provides further support for evidence showing that poverty is a major risk factor for mental health disorders in LMICs (Patel & Kleinman, 2003; Author et al, 2010; Author et al, 2011; Author, 2014).…”
Section: Discussionsupporting
confidence: 52%
“…It has long been recognized that social determinants such as socioeconomic status (SES) have a direct relationship with health outcomes (Marmot et al, 1991; Mackenbach et al, 1997) including mental disorders (Weich & Lewis, 1998; Lorant et al, 2003; Author et al, 2010; Richardson et al, 2015). Increasing absolute material wealth strongly predicts better mental health outcomes and life expectancy within countries, but does not explain differences in these outcomes between high-income countries (Wilkinson & Pickett, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We included complex variables, such as residency ZIP codes and attending doctor. ZIP codes can act as a surrogate of neighborhood socioeconomic characteristics, which has been shown to be associated with multiple disease and health behaviors (3638). The performance of attending doctors can potentially be a factor of postoperative outcomes as well (39, 40).…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of patients’ neighborhoods such as elevated poverty rates, low educational attainment, or unstable housing may reflect psychosocial stressors and reduced access to resources (e.g, transportation, childcare) which can undermine treatment participation or moderate treatment response. Systematic reviews of epidemiologic studies have reported mixed findings regarding whether individuals who live in more socioeconomically disadvantaged neighborhoods are at increased risk for depression . However, neighborhood income levels have been associated with antidepressant adherence, which could result in improved treatment outcomes among patients from neighborhoods with higher incomes.…”
Section: Introductionmentioning
confidence: 99%